Using TEI XML Schema to Encode the Structures of Sarawak Gazette - Tze-Min, Fong; Bali, Ranaivo-Malançon (IJSSH, 2015)
Automatic extraction of information from old printed documents which have been digitised injudiciously will end up with a lot human corrections. To overcome the problem, one possible solution is to annotate the documents with some markups. This paper presents the encoding of the digitised sample of Sarawak Gazette published from 1903 until 1939 using the standard TEI XML schema. The output of the work is a set of six TEI XML templates that is considered to represent the different layout structures found in the studied samples.